DOI: 10.31274/etd-180810-4409
|View full text |Cite
|
Sign up to set email alerts
|

Textual silences and the (re)presentation of black undergraduate women in higher education journals: a critical discourse analysis

Abstract: Throughout history, media portrayals have shaped what is deemed important in a culture and the way people view "others" (McCombs & Shaw, 1972). Popular magazines, movies, music, and the news provide people with information regarding the needs and behaviors of individuals and groups; therefore, when real-life interactions with these populations are limited, media portrayals can significantly influence perception. Research has shown that in the U.S., media portrayals of people of color, women, and specifically B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…The superwoman ideal promotes the expectations of Black women as selfless, hardworking, and strong (West et al, 2016). When BWU are perceived as super women, they are seen as having the ability to persist at any cost, even if that cost is their own self-esteem and mental health (Everett & Croom, 2017). The idea that Black women are impermeable to vulnerability, the psychological and emotional impact of academic struggles, and microaggressive attacks on their intellect is harmful to their identities and self-concepts .…”
Section: Bwus' Identity Construction At Pwismentioning
confidence: 99%
“…The superwoman ideal promotes the expectations of Black women as selfless, hardworking, and strong (West et al, 2016). When BWU are perceived as super women, they are seen as having the ability to persist at any cost, even if that cost is their own self-esteem and mental health (Everett & Croom, 2017). The idea that Black women are impermeable to vulnerability, the psychological and emotional impact of academic struggles, and microaggressive attacks on their intellect is harmful to their identities and self-concepts .…”
Section: Bwus' Identity Construction At Pwismentioning
confidence: 99%
“…What research has shown regarding handbook language is that the language of the handbook can be the primary focus of social change and that the discourse is not inclusive without the explicit rhetoric of those who aim for inclusion (Everett, 2015).…”
Section: Previous Research On School Handbooksmentioning
confidence: 99%